Vecm Analysis Of Sharia Financing On Roa Of Sharia Commercial Banks In Indonesia - Andrie Firmansyah; Nasrulloh (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the effect of murabahah, ijarah, and qard financing on the financial performance of Islamic commercial banks in Indonesia, as measured by Return on Assets (ROA) during the period 2015–2023. This research employs a quantitative approach using time series data obtained from Islamic Banking Statistics published by the Financial Services Authority (OJK). The analytical method used is Vector Autoregression (VAR) and Vector Error Correction Model (VECM), supported by Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD). The results indicate that, both in the short term and long term, murabahah financing has a significant and positive effect on ROA. Meanwhile, ijarah and qard financing show a weak and insignificant effect on ROA. The findings suggest that murabahah financing plays a dominant role in improving the financial performance of Islamic commercial banks. This study also highlights the importance of expanding research variables by including macroeconomic factors and applying causality analysis in future studies.